Heterogeneous impacts of conditional cash transfers: evidence from Nicaragua - Ana C. Dammert (Institute for the Study of Labor (IZA), 2008)
In the last decade, the most popular policy tool used to increase human capital in developing countries has been the conditional cash transfer program. A large literature has shown significant mean impacts on schooling, health, and child labor. This paper examines heterogeneous effects using random-assignment data from the Red de Proteccion Social in rural Nicaragua. Using interactions between the targeting criteria and the treatment indicator, estimates suggest that children located in more impoverished localities experienced a larger impact of the program on schooling in 2001, but this finding is reversed in 2002. Estimated quantile treatment effects indicate that there is considerable heterogeneity in the impacts of the program on the distribution of food expenditures, as well as total expenditures. In particular, households at the lower end of the expenditure distribution experienced a smaller increase in expenditures. This paper also presents evidence of the rank invariance assumption to help clarify the interpretation of the quantile treatment effect in the development literature context.
urn:nbn:de:101:1-20080828135
Keywords: O15; 330; Nicaragua; conditional cash transfers; quantile treatment effect; Sozialhilfe; Konditionen; Kinder; Bildungsverhalten; Bildungspolitik; Wirkungsanalyse; Verbraucherausgaben; Nicaragua